Match performance and physical capacity of players in the top three competitive standards of English professional soccer - Bradley, P. S.; Carling, C.; Gomez Diaz, A.; Hood, P.; Barnes, C.; Ade, J.; Boddy, M.; Krustrup, P.; Mohr, M. (Human Movement Science, 2013)
The aim of this study was to compare the match performance and physical capacity of players in the top three competitive standards of English soccer. Match performance data were collected from players in the FA Premier League (n = 190), Championship (n = 155) and League 1 (n = 366) using a multiple-camera system. In addition, a selection of players from the Premier League (n = 56), Championship (n = 61) and League 1 (n = 32) performed the Yo-Yo intermittent endurance test level 2 (Yo-Yo IE2) to determine physical capacity. Players in League 1 and the Championship performed more (p < .01) high-intensity running than those in the Premier League (Effect Size [ES]: 0.4-1.0). Technical indicators such as pass completion, frequency of forward and total passes, balls received and average touches per possession were 4-39% higher (p < .01) in the Premier League compared to lower standards (ES: 0.3-0.6). Players also covered more (p < .05) high-intensity running when moving down (n = 20) from the Premier League to the Championship (ES: 0.4) but not when players moved up (n = 18) standards (ES: 0.2). Similar Yo-Yo IE2 test performances were observed in Premier League, Championship and League 1 players (ES: 0.2-0.3). Large magnitude relationships (p < .05) were observed between Yo-Yo IE2 test performances and the total and high-intensity running distance covered in both Championship (r = .56 and .64) and Premier League matches (r = .61 and .54). The data demonstrate that high-intensity running distance was greater in players at lower compared to higher competitive standards despite a similar physical capacity in a subsample of players in each standard. These findings could be associated with technical characteristics inherent to lower standards that require players to tax their physical capacity to a greater extent but additional research is still required to confirm these findings.